2014
DOI: 10.3390/toxins6020523
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Multi-Mycotoxin Exposure in Southern Italy by Urinary Multi-Biomarker Determination

Abstract: Human exposure assessment to deoxynivalenol (DON), aflatoxin B1 (AFB1), fumonisin B1 (FB1), zearalenone (ZEA) and ochratoxin A (OTA) can be performed by measuring their urinary biomarkers. Suitable biomarkers of exposure for these mycotoxins are DON + de-epoxydeoxynivalenol (DOM-1), aflatoxin M1 (AFM1), FB1, ZEA + α-zearalenol (α-ZOL) + β-zearalenol (β-ZOL) and OTA, respectively. An UPLC-MS/MS multi-biomarker method was used to detect and measure incidence and levels of these biomarkers in urine samples of 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
169
6
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(189 citation statements)
references
References 40 publications
13
169
6
1
Order By: Relevance
“…Results of epidemiological studies on mycotoxins using biomonitoring have been reported in the past two decades (Duarte et al, 2012;Ediage et al, 2013;Gilbert et al, 2001;Pena et al, 2006;Rubert et al, 2011;Turner et al, 2010;Van der Westhuizen et al, 2011). These studies were based on only one urine sample per person, and thus the collection can be fairly easy (Heyndrickx et al, 2014;Solfrizzo et al, 2014). However, authors of a recent study, whereby the exposure to DON in three EU countries using these urinary biomarkers was assessed, strongly advice to collect 24-hours urine (Brera et al, 2015).…”
Section: Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations
“…Results of epidemiological studies on mycotoxins using biomonitoring have been reported in the past two decades (Duarte et al, 2012;Ediage et al, 2013;Gilbert et al, 2001;Pena et al, 2006;Rubert et al, 2011;Turner et al, 2010;Van der Westhuizen et al, 2011). These studies were based on only one urine sample per person, and thus the collection can be fairly easy (Heyndrickx et al, 2014;Solfrizzo et al, 2014). However, authors of a recent study, whereby the exposure to DON in three EU countries using these urinary biomarkers was assessed, strongly advice to collect 24-hours urine (Brera et al, 2015).…”
Section: Characteristicsmentioning
confidence: 97%
“…Samples can be used for analysis of multiple contaminants; allows estimation of chronic and acute exposure to contaminants. and body weight (Gratz et al, 2014;Rodriguez-Carrasco et al, 2014;Sarkanj et al, 2013;Solfrizzo et al, 2014;Turner et al, 2008;Wallin et al, 2013;Warth et al, 2012). This re-calculation is only possible for toxins showing a rapid elimination and short mean residence time (like for example DON).…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of analytes studied simultaneously varied between four (Warth et al, 2012a) and 33 (Heyndrickx et al, 2015) compounds. The use of β-glucuronidase-assisted hydrolysis (in order to increase the levels of the parent toxins) (Ahn et al, 2010;Shephard et al, 2013;Solfrizzo et al, 2011Solfrizzo et al, , 2014Wallin et al, 2015), immunoaffinity columns (IAC) (Ahn et al, 2010;Rubert et al, 2011;Shephard et al, 2013;Solfrizzo et al, 2011Solfrizzo et al, , 2014Wallin et al, 2015) and solid-phase extraction (SPE) (Heyndrickx et al, 2015;Njumbe Ediage et al, 2012;Rodríguez-Carrasco et al, 2014a,b;Shephard et al, 2013;Solfrizzo et al, 2011Solfrizzo et al, , 2014Wallin et al, 2015) were applied by some authors as sample preparation and clean-up procedures. However, some studies have also successfully used the so-called dilute and shoot approach by omitting any cleanup procedure (Abia et al, 2013;Ezekiel et al, 2014;Gerding et al, 2014Gerding et al, , 2015Heyndrickx et al, 2015;Shephard et al, 2013;Warth et al, 2012a,b).…”
Section: Main Challenges In Exposure Assessment To Multiple Mycotoxinsmentioning
confidence: 99%
“…All over the world, recent surveys highlight the fact that humans are more frequently exposed to multiple than to single mycotoxins (De Ruyck et al, 2015;Grenier and Oswald, 2011;Solfrizzo et al, 2014;Stoev, 2015) given the natural co-occurrence of mycotoxins in food and the globalisation of food markets (McKean et al, 2006). Furthermore, climate changes towards an increase of temperature and humidity in certain European regions are expected to favour the growth of contaminating fungi, thereby increasing the likelihood of food commodities contamination with mycotoxins (Paterson and Lima, 2010).…”
Section: Introductionmentioning
confidence: 99%